2009
DOI: 10.3171/2008.4.17537
|View full text |Cite
|
Sign up to set email alerts
|

Early brain tumor metastasis reduction following Gamma Knife surgery

Abstract: Gamma Knife surgery can offer patients early substantial volume reduction in many brain metastases. In instances in which early volume reduction of limited intracranial disease is desired, GKS may be used alone or before whole brain radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 25 publications
1
25
0
3
Order By: Relevance
“…21,26 In addition, a reduction in tumor volume after SRS has been documented to occur in 46% of NSCLC metastases. 7 Tumor volume is known to impact neurological and cognitive functioning and is likely a more important survival factor than number of tumors.…”
Section: Discussion Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…21,26 In addition, a reduction in tumor volume after SRS has been documented to occur in 46% of NSCLC metastases. 7 Tumor volume is known to impact neurological and cognitive functioning and is likely a more important survival factor than number of tumors.…”
Section: Discussion Survivalmentioning
confidence: 99%
“…A median of 2 metastases (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] were treated at each radiosurgical procedure. The median marginal dose was 18 Gy (range 10-22 Gy) and the maximum dose was 34 Gy (range 20-50 Gy).…”
Section: Radiosurgery Techniquementioning
confidence: 99%
“…Within this timeframe, studies have shown SRS to achieve a 90% radiographic lesional control rate, defined as lesions with stable or decreasing size. [6][7][8][9][10] However, transient increases in the size of up to 12% of lesions have been reported, and 9% of lesions at 4-year follow-up can be larger than they were at the time of treatment. 6,8 Lesion control rates are reported to vary by time since radiosurgery, pathology, lesion size, and treatment dose.…”
mentioning
confidence: 99%
“…[6][7][8][9][10] However, transient increases in the size of up to 12% of lesions have been reported, and 9% of lesions at 4-year follow-up can be larger than they were at the time of treatment. 6,8 Lesion control rates are reported to vary by time since radiosurgery, pathology, lesion size, and treatment dose. [10][11][12][13][14] However, no single study has looked at all of these factors during serial follow-up imaging.…”
mentioning
confidence: 99%
“…Ильялова [31], проведение СРХГН (стереотаксическая радиохирургия гамма-ножом) позво-лило достичь стабилизации внутримозговых метастазов в 88,3% случаев, а у 93,3% больных получить паллиативный эффект в виде стабилизации или регресса неврологиче-ской симптоматики [31]. В работе Arnаldo Neves Da Silva [32] у 2 больных с метастазами РЯ до 4,1 см 3 путем облу-чения опухолей на аппарате Leksell Gamma Knife в СОД 45,8 Гр отмечено уменьшение опухолей на 15% и более.…”
Section: таблица 1 определение Rpa-класса (по Rtog 1997)unclassified